A Community Based Study on Breastfeeding Practices in A Rural Area of Uttarakhand - Vyas, Shaili; Sharma , Parul; Kandpal , S D; Semwal , Jayanti; Srivastava , Anurag; Nautiyal , Vipul (National Journal of Community Medicine, 2012)
Background: Breast feeding is the safest, least allergic and best infant feeding method. It has nutritional, immunological, behavioral and economic benefits and also provide desirable mother infant bonding. Despite the demonstrated benefits of breastfeeding, breastfeeding prevalence and duration in many countries are still lower than the international recommendation of exclusive breastfeeding for the first six months of life . Objective: To know breast feeding practices of mothers with a view to strengthen these practices for improving the health of infants. Materials & methods: Community Based Cross sectional study was conducted in the field practice area of Rural Health Training Centre. 500 mothers having children between 0-3years age group were included in the study .Self administered questionnaire was used to collect information on breastfeeding practices in the initial six months of birth of the child. Results: The study findings revealed that majority of children were breastfed (93.6%). Initiation of breastfeeding within an hour was practiced by only a few mothers (21.37%). Only 5.13% babies were exclusively breastfed till six months. Prelacteal feeds & colostrum was given to most of them i.e. 66.03% & 87.18%. Conclusion: This shows that undesirable cultural practices such as giving pre-lacteals, late initiation of breast feeding are still prevalent among the community & these should be discouraged by proper BCC activities. For successful feeding, mothers need active support, care & privacy during pregnancy & following birth, not only of their families & communities but also of the entire health system.